Influence of body mass on maximal oxygen uptake: effect of sample size - Jensen, K.; Johansen, L.; Secher, N. H. (European Journal of Applied Physiology, 2001)
Basal metabolic rate is scaled to body mass to the power of 0.73, and we evaluated whether a similar scaling applies when the O2 transport capacity of the body is challenged during maximal exercise (i.e. at maximal O2 uptake, V˙O2max). The allometric relationship between V˙O2max and body mass (y=a · xb, where y is V˙O2max and x is body mass) was developed for 967 athletes representing 25 different sports, with up to 157 participants in each sport. With an increasing number of observations, the exponent approached 0.73, while for entilation the exponent was only 0.55. By using the 0.73 exponent for V˙O2max, the highest value [mean (SD)] for the males was obtained for the runners and cyclists [234 (16) ml · kg-0.73 · min-1], and for the females the highest value was found for the runners [189 (14) ml · kg-0.73 · min-1]. For the females, aerobic power was about 80% of the value achieved by the males. Scaling may help both in understanding variation in aerobic power and in defining the physiological limitations of work capacity.